Focus Group Discussion dan Konsultasi Publik Penyusunan Rancangan Awal Rencana Pembangunan Jangka Panjang Kabupaten Buru Selatan 2025-2045 - Ega, La; Irwanto, Irwanto; Boreel, Aryanto; Tupan, Johan Marcus (Yayasan Daarul Huda Kruengmane, 2024)
Focus Group Discussion (FGD) and public consultations for the preparation of the Preliminary Draft Regional Long Term Development Plan (RPJPD) for South Buru Regency 2025-2045 are strategic steps in formulating a long-term development vision that is in line with the National Long Term Development Plan (RPJPN) 2025-2045 and Maluku Province RPJPD 2025-2045. FGD activities and public consultations are carried out to identify specific regional issues and needs, collect accurate information and data, develop solutions and strategies, and increase community participation and transparency in the planning process. The method for implementing FGDs and public consultations involves various stakeholders, including regional apparatus organizations (OPD), DPRD, community leaders, academics, business associations, NGOs and youth organizations. This activity aims to ensure comprehensive input so that the resulting plan is more accurate, inclusive and implementable. The results of FGDs and public consultations include identification of problems such as accessibility and connectivity, limited infrastructure, poverty, environmental damage and land conversion issues. The vision of South Buru Regency 2025-2045 is